Re-visiting the Leadership Gap: How to lead in a task-focused work system - Turnbull, Helen; Murphy, Liam (GILE Journal of Skills Development, 2024)
The organisational focus on workplace automation is fuelling the evolution of the labour market towards task focused work systems, and an emerging gig economy. This evolution creates new demands on organisational leaders to introduce flexible and agile management techniques, whilst maintaining a strategic focus on upskilling and reskilling their employees for a digitalised world. We revisit our previous GJSD paper, “Mind the leadership gap”, to further emphasise these aspects of the changing work environment and introduce 1. Their potential influence on organisational belonging, and 2. The resultant impact on leadership styles and skills. This paper presents a short synthesis of the complex challenges faced by leaders within such an operating environment. This is followed by four further proposals for the future research agenda along with two suggested research methods which enhance our previous call to action on the leadership gap.